2019
DOI: 10.1002/ejic.201900631
|View full text |Cite
|
Sign up to set email alerts
|

Bis(benzoxazol‐2‐yl)methanes Hounding NacNac: Varieties and Applications in Main Group Metal Coordination

Abstract: Inspired by the well‐established class of β‐diketiminate or NacNac ligand scaffolds, the systematic building of ligand platforms mimicking its structural features and shielding abilities represents an exciting challenge. One of our focuses in the past decade has been the development of bis(benzheterocyclo)methanes, ‐amines and –phosphanes featuring additional donor‐sites in the ligand backbone as well as increasing steric bulk adjacent to the coordination pocket. This article addresses the variety of obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…The origin of the compounds published by us earlier, as well as the pK a measurement methods, can be found from the following references: [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The most comprehensive method description is given in ref [5].…”
Section: Compounds and Pk A Measurement Methodsmentioning
confidence: 99%
“…The origin of the compounds published by us earlier, as well as the pK a measurement methods, can be found from the following references: [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The most comprehensive method description is given in ref [5].…”
Section: Compounds and Pk A Measurement Methodsmentioning
confidence: 99%
“…18 Furthermore, this system offers an additional oxygen donor site for various coordination motifs. 19 The extension of the aromatic a. M. Sc. Christina M. Legendre, M. Ed.…”
Section: Introductionmentioning
confidence: 99%
“…Additional substitution along the aromatic system allows steric and geometry control in the third dimension. 19,20 Effective magnetic and steric shielding of the metal atom not only quenches the intermolecular metal-metalcoupling effects but also increases complex stability. 21 Apart from implementation in main group chemistry, 19,22,23 this system has so far neither been employed nor studied for dmetal chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings substantiate the observation of mixed Li–Cl/Li–CH 3 dimers in solution as presented by Maddaluno et al The increasing electrostatic contribution in smaller aggregates as revealed by our experimental and theoretical analyses now provides additional substantiation to these findings. The addition of halide salts to organometallics to achieve modified reactivity is a synthetic concept of growing interest, even thrivingly shifting the notoriously pyrophoric organolithiums to noninert aqueous conditions. A detailed knowledge of the interaction of the influence of those mixed organometallics will help to understand their reactivity and will broaden their synthetic application.…”
Section: Resultsmentioning
confidence: 99%